How can climate predictions improve sustainability of coastal fisheries in Pacific Small-Island Developing States?. (February 2018) - Dunstan, Piers K.; Moore, Bradley R.; Bell, Johann D.; Holbrook, Neil J.; Oliver, Eric C.J.; Risbey, James; Foster, Scott D.; Hanich, Quentin; Hobday, Alistair J.; Bennett, Nathan J.
Abstract: Climate and weather have profound effects on economies, the food security and livelihoods of communities throughout the Pacific Island region. These effects are particularly important for small-scale fisheries and occur, for example, through changes in sea surface temperature, primary productivity, ocean currents, rainfall patterns, and through cyclones. This variability has impacts over both short and long time scales. We differentiate climate predictions (the actual state of climate at a particular point in time) from climate projections (the average state of climate over long time scales). The ability to predict environmental conditions over the time scale of months to decades will assist governments and coastal communities to reduce the impacts of climatic variability and take advantage of opportunities. We explore the potential to make reliable climate predictions over time scales of six months to 10 years for use by policy makers, managers and communities. We also describe how climate predictions can be used to make decisions on short time scales that should be of direct benefit to sustainable management of small-scale fisheries, and to disaster risk reduction, in Small-Island Developing States in the Pacific